2005
DOI: 10.1055/s-2005-870154
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Insufflation in Colonoscopy: Safe and Effective in Sedated Patients

Abstract: This study indicates that CO2 insufflation reduces pain and is safe to use in colonoscopy for sedated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
127
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 8 publications
2
127
1
4
Order By: Relevance
“…As it appeared that there was less bloating and likely less pain after procedures using CO2 for gut distension compared to air [2] , randomized controlled trials (RCTs) were performed to compare post-procedure pain when using CO2 versus room air as the insufflation agent. The results of all of these RCTs were unambiguous, with significantly less pain reported after CO2 colonoscopy [3][4][5][6][7] . For other endoscopic procedures also, CO2 was found to be superior to air: (1) for double balloon enteroscopy, small bowel intubation is deeper [8] ; (2) for endoscopic retrograde cholangio-pancreatography (ERCP), postprocedural pain is less [9,10] ; and (3) for complex colorectal procedures (endoscopic submucosal dissection), fewer sedative drugs are required [11] .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…As it appeared that there was less bloating and likely less pain after procedures using CO2 for gut distension compared to air [2] , randomized controlled trials (RCTs) were performed to compare post-procedure pain when using CO2 versus room air as the insufflation agent. The results of all of these RCTs were unambiguous, with significantly less pain reported after CO2 colonoscopy [3][4][5][6][7] . For other endoscopic procedures also, CO2 was found to be superior to air: (1) for double balloon enteroscopy, small bowel intubation is deeper [8] ; (2) for endoscopic retrograde cholangio-pancreatography (ERCP), postprocedural pain is less [9,10] ; and (3) for complex colorectal procedures (endoscopic submucosal dissection), fewer sedative drugs are required [11] .…”
Section: Introductionmentioning
confidence: 77%
“…Contraindications to the use of CO2 are limited to severe chronic obstructive pulmonary disease (if CO2 is absorbed at a rate exceeding its respiratory elimination, this leads to CO2 retention and pulmonary acidosis) [24] . Provided that this contraindication is observed, Bretthauer et al [3] have shown that, although pCO2 levels increase during colonoscopy and ERCP (due to the effect of sedative drugs), this increase is no more important with CO2 than with air insufflation [4,9] . Finally, the cost of an insufflator was cited as a limiting factor by endoscopists who attempted to implement the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be associated with the superior recovery quality of CO 2 insufflation compared with room air insufflation in colonoscopy (36). Therefore, when compared with air insufflation, CO 2 insufflation is expected to reduce the volume of residual gas following ESD, which is a primary cause of patient discomfort associated with this procedure, and consequently prevent the development of abdominal symptoms and problems associated with ESD (5,(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study also reported that CO 2 insufflation was safe and effective during colorectal ESD (15). As CO 2 is absorbed faster than air and is rapidly eliminated through the lungs, CO 2 insufflation is expected to reduce residual gas in both the small and large bowels following ESD, and consequently reduce the abdominal symptoms and complications associated with ESD (15,(22)(23)(24)(25)(26)(27)(28)(29)(30). However, to the best of our knowledge, detailed and quantitative examinations evaluating the effects of CO 2 insufflation on residual gas in the gastrointestinal tract following colorectal ESD have not been performed.…”
Section: Introductionmentioning
confidence: 99%